Binary gravitational search algorithm (BGSA) for solving feature selection problem - Rao Banoth, Nageswara; Dara y, Suresh; Jagadeeshwara Reddy, M; P. Singh, R (International Journal of Engineering and Technology, 2018)
In previous years, dierent Lateral thinking optimization techniques have been developed based on evolutionary computation. Many of these methods are inspired by spill out behaviors in nature. In this Paper, a new optimization algorithm based on the law of gravity and mass interactions named as Gravitational Search Algorithm (GSA) is discussed for solving feature selection. In GSA, the searcher agents are a collection of masses which will interact with each other based on the law of motion and Newtonian gravity which gives the binary evolutionary optimized high performance. The detailed feature selection has been discussed in this paper and The GSA method has been compared with some wellknown optimized search methods such as GA (Genetic Algorithm), PSO (Particle Swarm Optimization).Â Â